2021
DOI: 10.3390/jof7050386
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal-Resistant Filamentous Fungi as Potential Mercury Bioremediators

Abstract: Filamentous fungi native to heavy metals (HMs) contaminated sites have great potential for bioremediation, yet are still often underexploited. This research aimed to assess the HMs resistance and Hg remediation capacity of fungi isolated from the rhizosphere of plants resident on highly Hg-contaminated substrate. Analysis of Hg, Pb, Cu, Zn, and Cd concentrations by X-ray spectrometry generated the ecological risk of the rhizosphere soil. A total of 32 HM-resistant fungal isolates were molecularly identified. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 109 publications
(171 reference statements)
2
23
0
1
Order By: Relevance
“…AHM96 as compared to their dead counterparts at 40 °C ( Figure 2 ). In accordance with our findings, Vacar et al. (2021) reported that live biomasses of a great number of filamentous fungi native to heavy metals (HMs) polluted region including Didymella glomerata , Phoma costaricensis , Stagonosporopsis sp., Cladosporium sp., Aspergillus sp., Penicillium sp., Mortierella sp., Cadophora malorum , Sarocladium sp., Fusarium sp.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…AHM96 as compared to their dead counterparts at 40 °C ( Figure 2 ). In accordance with our findings, Vacar et al. (2021) reported that live biomasses of a great number of filamentous fungi native to heavy metals (HMs) polluted region including Didymella glomerata , Phoma costaricensis , Stagonosporopsis sp., Cladosporium sp., Aspergillus sp., Penicillium sp., Mortierella sp., Cadophora malorum , Sarocladium sp., Fusarium sp.…”
Section: Resultssupporting
confidence: 92%
“…Their cell membrane consists of a thin, double-layered sheet of lipids, mainly with phospholipids and sterols (about 40% of membrane content) and protein molecules (about 60%), which reveals excellent heavy metals binding properties ( Ayele et al., 2021 ). Filamentous fungi native to areas contaminated with heavy metals (HMs) have abundant bioremediation potential, yet they often remain untapped ( El-Gendy et al., 2011 , 2017 ; Sharma et al., 2022 ; Vacar et al., 2021 ). Many fungal-derived biomass of fungi as Aspergillus niger , Penicillium brevicompactum , Termitomyces clypeatus , Penicillium simplicissimum , Aspergillus fumigatus , Saccharomyces cerevisiae are widely applied as sorbents for heavy metals and other pollutants from wastewater because of their high adsorption capability and affinity, low cost, selectivity, their availability in large quantities and their eco-friendly nature however the another techniques have inherent restrictions such as large amount of sludge generation, sensitive operating conditions, low efficiency and costly disposal ( Rastegari et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that the mycelium of fungi can remediate a variety of chemical, heavy metal, and bacterial contaminants from terrestrial and aquatic environments (Akhtar & Mannan, 2020; Taylor & Stamets, 2013; Văcar et al, 2021). Mycelium are the underground network of hyphae of the fungus and are different from the better‐known fruiting body (the mushroom).…”
Section: Mycofiltrationmentioning
confidence: 99%
“…Pollution entering surface waters from non-point sources are not directly regulated through the CWA, and instead, the EPA uses the ability to establish WQC to try and reduce contamination from non-point sources. However, there has been limited progress on improving water quality from non-point sources because of issues like failing infrastructure (Divers et al, 2014;Hopkins & Bain, 2018), agricultural practices and legacy nutrients (Stets et al, 2020;van Meter et al, 2018), and industrial contamination (Silbergeld, 2017). We may underestimate the full impact of the CWA on our waterways in part because of our inability to fully quantify the economic benefits, including health impacts .…”
Section: Box 1 the Clean Water Actmentioning
confidence: 99%
“…Suda doğal olarak 1 mg/L'den daha az miktarda bulunan ağır metallerin önemli kimyasal etkileri vardır [3]. Bazı metallerin belirli bir düzeyin üzerinde alınması insanlarda toksik etkilere neden olurken, düşük düzeylere uzun süre maruz kalınması çeşitli alerjik reaksiyonlarla birlikte kansere neden olabilmektedir [4]. Cıva, bakır, nikel, kurşun, krom gibi metaller toksik ağır metallerdir ve çevreye bırakıldıklarında toprakta birikerek çevreye ve canlılara önemli zararlar verirler [5].…”
Section: Introductionunclassified